The Applicable Dental Age Estimation Methods for Children and Adolescents in Indonesia - Arofi Kurniawan; An'nisaa Chusida; Nur Atika; Tito Krisna Gianosa; Mohammad Denis Solikhin; Mieke Sylvia Margaretha; Haryono Utomo; Maria Istiqomah Marini; Beta Novia Rizky; Beshlina Fitri Widayanti Roosyanto Prakoeswa; Aspalilah Alias; Anand Marya (Hindawi Limited, 2022)
Indonesia is an archipelagic country bordered by tectonically active zones with intense seismicity and volcanism. This condition is often associated with a high-risk situation of disasters in Indonesia. Forensic identification is a necessary procedure to reveal an individual's identity. An identity, including sex and age, is needed to build a conclusion of human identification. Dental age estimation is a subfield of forensic odontology which focuses on establishing an individual's age. Tooth development, biochemical, and postformation changes are the parameters for estimating dental age. This review discusses the applicable dental age estimation method for children and adolescents in Indonesia. Several articles that have previously studied dental age estimation in Indonesia were reviewed for this manuscript. On reviewing these articles, it was found that the Demirjian method, the Willems method, and the Al Qahtani method are useful in this population with higher accuracy than other methods.